Impact of Alternative Feed Ingredients and Feeding Strategies on Growth, Muscle Morphology, and Fillet Quality of Genetically Selected Gilthead Seabream (Sparus aurata) in a Long-Term Feeding Trial - Paula Sarmiento; Pedro L. Castro; Rafael Ginés (Animals)
Aquaculture advancement depends on alternative raw materials to reduce reliance on fishmeal (FM) and fish oil (FO) from extractive fisheries. Strategies like restricted feeding reduce costs and improve sustainability by minimizing feed waste and enhancing water quality, while selective breeding boosts growth and adapts fish to innovative diets. However, these measures may affect quality and shelf life. Gilthead seabream selected for high growth or non-selected were fed in 500 L tanks for 300 days until apparent satiety (AS) or with food restrictions (85AS or 65AS) using a control diet with low FM and FO balanced with vegetable ingredients, and an alternative diet (ALT) where FM was substantially replaced with insect, poultry by-product, feather, and porcine blood meals, while FO was completely replaced by microalgae, poultry, and salmon by-product oils. The ALT diet improved EPA + DHA levels, n-3/n-6 ratio, and fillet hardness. The selected fish outperformed the non-selected ones in growth and were more resilient to ALT diet and feeding restrictions. The 85AS feeding strategy optimized fillet quality by preventing lipid accumulation and muscle adaptations, as observed with the other feeding strategies. Combining sustainable feed formulations, genetic selection, and moderate feed restriction enables a viable, long-term strategy for high-quality, environmentally responsible seabream farming.